Marine-Lenhart Syndrome: Case Report, Diagnosis, and Management - Danielle Neuman; Russ Kuker; Francesco Vendrame (Case Reports in Endocrinology)
The coexistence of thyroid functioning nodules and Graves’ disease is called Marine-Lenhart syndrome. This condition is estimated to occur in 0.8-2.7% of patients with Graves’ disease with few cases reported in the literature. Criteria for the diagnosis are not well defined. Here, we present a case of hyperthyroidism characterized by the presence of stimulating TSH receptor antibodies and severe bilateral exophthalmos. A thyroid uptake and scan revealed an elevated 24-hour iodine-131 uptake and a discrete hot nodule in the upper pole of the right lobe which was also observed with a thyroid ultrasound. The patient was diagnosed with Marine-Lenhart syndrome complicated by thyroid eye disease and was treated with methimazole followed by thyroidectomy and orbital decompression. We review the existing literature and propose criteria for the diagnosis and treatment of this condition.